Islam as Discursive Tradition: The Reception of the Qur’an and Hadith as Pattula’ Bala’ in Bugis Society - Amir, Abdul Muiz (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2020)
This article examines the reception of the pattula’ bala’ in the tradition of the Bugis Muslim community. The tradition is important to study because it is still trapped in a theological debate regarding its position as part of acculturation. This study uses field data sources collected through observation, interviews, and documentation. Besides, literature data sources are also used to trace the history of hadith and the history of Islamic civilization. The data is processed and analyzed using reception and genealogy to find the historical connection between Islamic teachings and local traditions. It argues that the tradition of the pattula’ bala’ perceived by the Bugis Muslim community was discursive tradition, because they believed it based on transmitted from the Hadith, the practice of Sahaba, and other works of literature from the scholars. Besides, the tradition is not only as a tabarruk but also functions as a panoptic that motivates its users to be more active in practicing worship and avoiding all immoral acts.